The Chinese Eastern Railway: geostrategic heritage from the turn of the twentieth century in Northeast China - Qi Li; Daping Liu; Jusheng Song (Journal of Asian Architecture and Building Engineering, 2023)
The Chinese Eastern Railway (CER) is a 2,489 kilometers-long infrastructure network constructed by Russia in Northeast China at the turn of the twentieth century, which is still actively in use nowadays. A large number of architectonic structures, as important geostrategic heritages, are placed on both sides of the track. However, most of them had fallen into disrepair because the value of these diverse tangible elements remains under-appreciated through the years. By discerning and analyzing historical documents, this paper clarified and synthesized the background and construction process of the CER. Moreover, a full-scale field survey was conducted, from which nearly 2000 existing engineering facilities and buildings were discovered and documented. Based on systematic functional classification and distribution statistics, they were marked, analyzed, and mapped. This research provides a comprehensive understanding of the CER and reveals its heritage values. In addition to constructing the regional culture of Northeast China, as a living heritage, the heritagisation process of the CER may be able to facilitate and reflect the development of the current cultural heritage in China. Meanwhile, it is of significant importance to promote heritage use practically and improve the living environment for local people.